Use of parthenium weed as green manure for maize and mungbean production - Javaid, Arshad; Shah, M.B.M. (2008)
A pot experiment was conducted to evaluate the potential of parthenium weed (Partheniumhysterophorus L.), a noxious invasive alien weed, for use as green manure. Maize (Zea mays L.) andmungbean [Vigna radiata (L.) Wilczek] were used as test crops. The treatments employed were:control, recommended NPK fertilizers and 1%, 2%, 3% and 4% (w/w) parthenium green manure (freshweight basis). Parthenium was collected at 30–35 d growth stage prior to flowering. After the partheniummanure was mixed in the soil, the pots were irrigated and left for 30 d to allow decomposition. Maizeand mungbean were harvested 60 and 70 d after sowing, respectively. The highest root and shootbiomass in maize was obtained in 3% green manure treatment, which was significantly greater thanthat obtained in the control and equivalent to that obtained in the NPK fertilizer treatments. Effect ofboth NPK fertilizers and parthenium green manure on growth and yield of mungean was insignificant.
Keywords: Weeds; Maize; Mungbean; Fertilizers and manures